Soft Law in International Governance - Kwiatkowski, Paweł (Przegląd Prawniczy Uniwersytetu im. Adam Mickiewicza, 2017)
The purpose of the article is to assess how the provisions resulting from international programmatic norms in the field of human genetic data are implemented. The presented study, adopting the perspective of institutional rationalism extended to the paradigm of legalism, considers examples of the implementation of these standards in selected legal systems – Germany, the United States of America and France. The selection of the research paradigm is preceded by a theoretical introduction, which presents three ways of conceptualizing the notion of soft law in the legal sciences. Following an outline of this legal regime in positivism, and the theories of rationalization and constructivism, the author focuses on the provisions of the International Declaration on Human Genetic Data of 16 October, 2003, which are compared with the legislative initiatives of Germany, the United States of America and France, to show the influence that the choices of states has on selection of the implemented standards and how they are implemented.